Improving adoption of technologies and interventions for increasing supply of quality livestock feed in low- and middle-income countries - Balehegn, M.; Duncan, Alan J.; Tolera, Adugna; Ayantunde, Augustine A.; Issa, S.; Karimou, M.; Zampaligré, N.; André, K.; Gnanda, I.; Varijakshapanicker, Padmakumar; Kebreab, Ermias; Dubeux, J.; et al. (Elsevier, 2020)
The global increase in the demand for and production of animal-source foods (four-to five-fold increase between 1960 and 2015), which has been mostly concentrated in low- and middle-income countries (LMIC), provides smallholder livestock producers with an opportunity for improving their livelihoods and food and nutrition security. However, across livestock production systems in many LMIC, limited supplies and high cost of good quality feed severely constrains exploitation of this opportunity. In many of such countries, feeds and feeding-related issues are often ranked as the primary constraint to livestock production and increased consumption of animal-source foods. Here we review the complex biophysical, socio-economic and technological challenges related to improving quality feed supply and the reasons for generally low adoption of apparently proven feed enhancement technologies. We describe also successful interventions and conclude by recommending strategies for improving quality feed supply in LMIC that account for and overcome the prevailing challenges.